THE EFFECT OF COMPANY SIZE, LEVERAGE, CSR COSTS AND PROFITABILITY ON COMPANY VALUE: (In Manufacturing Industry Companies Listed on the Indonesia Stock Exchange 2017-2021) - Rahandhika Ivan Adyaksana (CV. Fahr Publishing, 2023)
This study aims to examine the effect of firm size, leverage, CSR costs and profitability on firm value. The sampling technique used in this study was purposive sampling. The number of samples in this study were 33 manufacturing companies listed on the Indonesia Stock Exchange for 2017-2021. The analysis technique used is multiple linear regression analysis. The results of the study show that firm size, leverage, CSR costs have no significant effect on firm value, while profitability has a significant positive effect on firm value. Keywords: company size, CSR costs, profitability, firm value